Service professionals’ classification of core and complementary tasks - Thomsen, Mette Kjærgaard; Jensen, Ulrik Thy (Politica, 2018)
Non-professional actors such as volunteers, service users, and citizens increasingly contribute to the production of public services. While increased involvement of such non-professionals is expected to have positive effects on the capacity of public organizations, few studies have explored professionals’ attitudes towards this trend. A central question concerns what services professionals see as core tasks that ought to be performed by professionals. We introduce a theoretical distinction between core and complimentary tasks and use a survey to investigate how health assistants employed at nursing homes classify various tasks along these two categories. Finally, we examine whether health assistants with a short and long education classify the same set of tasks differently, thereby shedding light on the importance of the degree of professionalism for the classification of concrete tasks as either core or complimentary.